Produção de biomassa e análise química do óleo essencial de Cymbopogon flexuosus sob omissão de nutrientes e adubação orgânica - Lopes, Vauvenargues (2017)
Cymbopogon flexuosus Stapf is a medicinal species belonging to the family Poaceae. The essential oil extracted from its leaves is widely used in the food, pharmaceutical, cosmetic and perfumery industries. The objective of this study was to study doses of organic fertilizers and omission of macronutrients in nutrient solution in the growth and production of chemical constituents of essential oil of C. flexuosus. The present work was divided in two experiments. In the first, different doses of cattle manure, quail and organic compost were evaluated. Organic fertilizers in different doses change the dry biomass gain, the content, the yield and the quality of the essential oil of C. flexuosus. The species responds positively to the increase of nutrients in the soil both in terms of production of secondary metabolites and vegetable growth. The highest growth and essential oil yield is obtained by fertilizing between 60 and 90 t ha-1 of quail manure. Neral content in the essential oil is increased with the use of 90 t ha-1 quail manure and geranial content with 30 and 90 t ha-1 of organic compound. In the second experiment, the effect of omission of macronutrients on growth, visual diagnosis, content and chemical composition of the essential oil of C. flexuosus in hydroponic culture was studied. The omissions of macronutrients caused visual symptoms of nutritional deficiency, common to other species. The limiting order of TDW was K = Mg> N = Ca = P> S. Potassium and magnesium were the most limiting macronutrients for biomass production. The highest content of essential oil was verified under omission of sulfur and the yield similar to the complete solution. The chemical analysis of the essential oil was quantitatively altered in hydroponic culture. The omission of P and N promoted an increase of citral contents.